Is COVID-19 a hoax? Correlation between beliefs related to COVID-19 and the use of preventive measures in India - Abdullah, Zoha; Anil, Alisha Ann; Dhanashekhar, Akshaya Keerthikha; Asik, Mohamed; Aji, Akshaya; Premnath, Parvathy (International Journal Of Community Medicine And Public Health, 2021)
Background: Following the personal protective and preventive measures are vital to the control and prevention of transmission. The populations’ beliefs and attitude related to coronavirus disease 2019 (COVID-19) have a direct impact on their practice of preventive measures. Therefore, this study was conducted to explore the beliefs, attitude and preventive practices related to COVID-19 among the general population of Chennai, Tamil Nadu. Methods: An online questionnaire with 12 questions concerning the beliefs, attitude and practice of preventive measures related to COVID-19 was distributed via social platforms. Data were entered in Microsoft Excel spreadsheet and analyzed using statistical package for social sciences (SPSS) software (version 21, IBM Corporation, Texas, USA). Bivariate analysis (Chi-square test) was used to assess the association between independent variables with each of the main outcomes of interest. Results: A total of 256 study subjects participated in this survey. About 69.9% believed in the existence of corona virus and >85% followed the government protocols. Social distancing and Frequent hand washing was chosen by majority of the study subjects (55.5% and 78.5% respectively) as the most effective measure to prevent viral transmission. Nearly 81.7% always wore a mask in public and 27.0% always kept >6 feet distance apart from others. Conclusions: The surveyed population has an acceptable level of positive beliefs, attitude, and good practices towards COVID-19. We recommend that emphasis should be placed on educating people belonging to lower education and income strata. Vulnerable populations who require proper health education and guidance for prevention and control of COVID-19 should be targeted.